Shoot tip culture as a potential tool in mutation breeding of the apple, Malus domestica cv Granny Smith - Pieterse, R. E.(Rachel Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1984.